Local Goverment Fiscal Risk Monitoring: Case Study In Bogor and Merauke Districts - A Faroby Falatehan; Yusman Syaukat; Dedi Budiman Hakim; D Sonny Priyarsono; Sri Mulatsih; Dwi Rachmina; Hastuti; Dea Amanda (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2022)
Some problems often faced by local governments in financing development are the gaps between regional needs that are not balanced with the fiscal capacity of the region so that a fiscal gap arises. Efforts are needed to carry out risk management through fiscal risks monitoring. This study was aimed to analyze and evaluate indicators of risks in regions that can affect local goverment fiscal. This study used various sub-indicators derived from five fiscal risk indicators, namely economic, financial, institutional, social and environmental indicators. Of the several indicators, the variables that pose a risk in Bogor District are water connection problem from water company (PDAM) that are still low (social indicators), budget allocation for the environment and unemployment issue, while in Merauke District, some problem that need to be considered are Infrastructure expenditure (economic indicators), local own-source revenue (PAD), fluctuated unemployment issue (economic indicators), regional independence ratios (financial indicators), social indicators particularly for water connection problems and budget allocation for the living environment.